Deliverable 5.13 Synthesis of the iAOS cloud infrastructure - Caumont, Hervé (Zenodo, 2022)
WP5 (Data integration and management) is tasked with designing and implementing evolution of the cloud platform and tools for the iAOS. This document gives a synthesis of the iAOS cloud infrastructure evolution during the project. The experience and challenges from the work include: (1) deploying and operating dedicated Cloud Platform infrastructure services, (2) integrating data repositories and data processing services based on these Cloud Platform infrastructure services, and (3) defining user-oriented applications powered by all these iAOS resources. As a result, the iAOS cloud platform offers services to access observations and derived parameters, including new observations from WP2-3-4. In addition, it offers seamless integration with geo-statistical methods for interpolation of spatiotemporal datasets, and services to store the generated datasets in iAOS enabled repositories. The report presents results on using the iAOS cloud platform to integrate multidisciplinary and distributed data repositories and to provide a set of tools for data analysis, transformation, and visualization. Selected applications established in WP6 have used the services and tools provided by the platform and have showcased the usefulness and functionality of the platform, as part of the benefit of enhanced integration of data from Arctic observing systems.